A NEW SPECIES OF MUK IA (CUCURBITACEAE) FROM SUMBA ISLAND, INDONESIA - Mentari Putri Pratami; Tatik Chikmawati; Rugayah Rugayah (BRIN Publishing (Penerbit BRIN), 2022)
PRATAMI, M. P., CHIKMAWATI, T. & RUGAYAH. 2022. A new species of Mukia (Cucurbitaceae) from Sumba Island, Indonesia. Reinwardtia 21(1): 35‒40. — Mukia sumbensis Pratami is described and illustrated as well as compared with its closely related species M. maderaspatana (L.) M.Roem. and M. leiosperma (Wight & Arn.) Wight. It differs in its tendril size, stem diameter, petiole hairiness, midrib indumentum on upper leaf surface, as well as in shape, margin, and surface of seed. Anatomically the leaf of the new species has two palisade layers, unlike the other two species which have only one layer.